Indian voters’ attitude and behavior toward a political brand for producing green products: a mediation model - Parul Yadav; Bhawna Agarwal; Jones Mathew (Future Business Journal)
Abstract This study explores the attitude–behavior relationship among voters for political party brands that use a sustainable or green marketing approach. A structural equation modeling is used to analyze data collected from 1771 respondents who are registered Indian voters in this case. A positive attitude toward a political brand is compared to intentions to vote for the same brand. According to the findings, political brands create a more environmentally friendly product in the form of green actions because doing so encourages consumers to think favorably of the political brand, which results in them voting for it. As a result, authors are able to identify a positive attitude–behavior relationship for political brands among voters.